TEACHERS’ PERCEPTIONS ON BRAINSTORMING AND IMAGINATION TECHNIQUES IN ENHANCING CREATIVITY IN DRAWING AMONG PRESCHOOL STUDENTS - Christty Joseph; Tan Choon Keong; Abdul Said Ambotang (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Teachers’ wisdom in selecting suitable teaching methods or techniques for students will influence the effectiveness of their instruction. Therefore, teachers need to develop teaching and learning strategies that are appropriate for students, particularly in fostering creativity in teaching and learning. Purpose: The main objective of this study is to examine the effectiveness of teaching brainstorming and imagination techniques in enhancing creativity in drawing among preschool students from the perspective of teachers. Methods: Interview sessions were conducted involving four preschool teachers from two schools in the Kota Belud District, Sabah, Malaysia. Results: The findings of the study, the teachers believed that brainstorming and imagination techniques could successfully enhance the creativity in drawing for preschool students. Conclusion: The teaching module using the brainstorming and imagination techniques will help to overcome teachers’ challenges and fulfils their needs to implement instruction that fosters creative skills in teaching.